2020
DOI: 10.1080/21645515.2020.1757990
|View full text |Cite
|
Sign up to set email alerts
|

Evervac: phase I/II study of immunogenicity and safety of a new adjuvant-free TBE vaccine cultivated in Vero cell culture

Abstract: Approximately 10,000 cases of tick-borne encephalitis (TBE), a serious disease of the central nervous system caused by tick-borne encephalitis virus (TBEV), are registered worldwide every year. Vaccination against TBE remains the most essential measure of preventing the disease. Unlike available TBE vaccines, a new inactivated lyophilized candidate vaccine Evervac is produced in Vero continuous cell culture and its final formulation does not include aluminum-based adjuvants. To study the safety and immunogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
0
12
0
2
Order By: Relevance
“…The structure of the production process of the vaccine CoviVac ( Figure 1 (A)) is rather similar to the ones presented for other inactivated vaccines against COVID-19 [ 26–28 ]. Beta-propiolactone was used to shorten the production process.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The structure of the production process of the vaccine CoviVac ( Figure 1 (A)) is rather similar to the ones presented for other inactivated vaccines against COVID-19 [ 26–28 ]. Beta-propiolactone was used to shorten the production process.…”
Section: Discussionmentioning
confidence: 65%
“…The drastic global shortage of the COVID-19 vaccines and successful clinical trials of the several inactivated preparations make this approach appropriate for inactivated vaccine producers. The Chumakov Center has successfully developed two inactivated vaccines on Vero cells against tick-borne encephalitis and poliomyelitis [22,23]. Therefore, the development of the COVID-19 vaccine was based on the established cell cultivating platform using previously established methods.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it differs from the available vaccines, Evervac vaccine is absence of aluminum hydroxide adjuvant. Animal experiments have shown that the application of this vaccine can significantly increase the geometric mean titer (GMT) of anti-TBEV antibodies in serum, and this vaccine has been proven to be safe and effective in the phase II of clinical study [ 112 ]. These valuable attempts suggest that factors of both pathogens and hosts should be evaluated in vaccine development.…”
Section: Vaccines Of Flavivirusmentioning
confidence: 99%
“…Recently, an aluminum hydroxide-free, inactivated whole virus TBEV vaccine (Evervac, TBEV-FE strain Sofjin) produced in a continuous Vero cell line was tested in a phase I/II clinical trial and showed comparable safety, tolerability and immunogenicity results to the TBE vaccine Moscow. However, this vaccine is not yet licensed [ 41 ]. The vaccination schedules of the TBEV vaccines are very time-consuming.…”
Section: Currently Available Vaccinesmentioning
confidence: 99%